7x-(4x-13)=40

Simple and best practice solution for 7x-(4x-13)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-(4x-13)=40 equation:


Simplifying
7x + -1(4x + -13) = 40

Reorder the terms:
7x + -1(-13 + 4x) = 40
7x + (-13 * -1 + 4x * -1) = 40
7x + (13 + -4x) = 40

Reorder the terms:
13 + 7x + -4x = 40

Combine like terms: 7x + -4x = 3x
13 + 3x = 40

Solving
13 + 3x = 40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 3x = 40 + -13

Combine like terms: 13 + -13 = 0
0 + 3x = 40 + -13
3x = 40 + -13

Combine like terms: 40 + -13 = 27
3x = 27

Divide each side by '3'.
x = 9

Simplifying
x = 9

See similar equations:

| 27/63 | | 3(2x-5)=44x-7 | | x+x+23+(x+23)/4=562 | | 4(4x-3)-6x=4(2x+3)-24 | | -20+2x=-12 | | -8x+9x=-1+7 | | -4(1+2r)-r=7(-r-4) | | 4(4x-3)-6x=4x+2(3x-6) | | x+25+4x=-34-4x-40 | | 6x+20+2x+4=90 | | 3x+3=4x+9 | | 6x+20+2x+4= | | 3(x-8)+x=4(x-7)+4 | | 25-(x+3)=2(2x+1) | | -5(m+1)-1=8m-7(7m+6) | | -150+5x=-4x+84 | | 2x-5=2x+6 | | 4x+10=6x-4 | | (8-10x*5x+4)=0 | | 5(6)+5(2)=5(6+2) | | 2(3x+1)=6x | | 21/48 | | X^2=3177 | | -24v^8-11v^6= | | 4/6m+5=12 | | -86+x=3 | | -12k^7+4k^8= | | 2y+3xy-8=5y+6 | | 4x-35=2x+41 | | -72=3d-11d | | 3x-15+2x+18=15 | | x-35=2x+41 |

Equations solver categories